Four Level Simulation of MOSFET. (1998) - Doja, M. N.; Moinuddin,; Kumar, Umesh
Abstract : In this paper a software (MOSOFT) has been developed for 4-level simulation of MOSFETS. This software simulates the device characteristics up to micron channel length and includes long channel, short channel, subthreshold and field dependent mobility degradation models.